Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1016/j.bmc.2008.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Selective A3 adenosine receptor antagonists derived from nucleosides containing a bicyclo[3.1.0]hexane ring system

Abstract: We have prepared 5′-modified derivatives of adenosine and a corresponding (N)-methanocarba nucleoside series containing a bicyclo[3.1.0]hexane ring system in place of the ribose moiety. The compounds were examined in binding assays at three subtypes of adenosine receptors (ARs) and in functional assays at the A 3 AR. The H-bonding ability of a group of 9-riboside derivatives containing a 5′-uronamide moiety was reduced by modification of the NH, however these derivatives did not display the desired activity as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

7
1

Authors

Journals

citations
Cited by 36 publications
(95 citation statements)
references
References 33 publications
5
90
0
Order By: Relevance
“…8 The corresponding 4′-truncated (N)-methanocarba nucleoside containing a racemic N 6 -(2-phenylcyclopropyl) substitution was found to be a selective A 3 AR antagonist (K i 1.3 nM). 13 The 1 S,2R diastereoisomer of 2 was ~10-fold more potent in binding to the hA 3 AR (K i 11.2 nM) than the corresponding 1 R ,2 S isomer. This N 6 substituent was also combined with C2-cyano or carboxamide substitution in a subsequent 9-riboside series resulting in a moderate reduction of A 3 AR affinity.…”
mentioning
confidence: 93%
“…8 The corresponding 4′-truncated (N)-methanocarba nucleoside containing a racemic N 6 -(2-phenylcyclopropyl) substitution was found to be a selective A 3 AR antagonist (K i 1.3 nM). 13 The 1 S,2R diastereoisomer of 2 was ~10-fold more potent in binding to the hA 3 AR (K i 11.2 nM) than the corresponding 1 R ,2 S isomer. This N 6 substituent was also combined with C2-cyano or carboxamide substitution in a subsequent 9-riboside series resulting in a moderate reduction of A 3 AR affinity.…”
mentioning
confidence: 93%
“…behaving as partial agonist or antagonist of this subtype. [24] Our docking of nucleoside analogues in the hA 3 AR homology model indicated that the absence of a hydroxymethyl or uronamide substituent at the 4′-position prevented these compounds from interacting with Thr94 (3.36). This residue is a conserved recognition point in agonist binding, and therefore the lack of this interaction was considered as a reason for the low efficacy profile of 4′-truncated nucleosides.…”
Section: Resultsmentioning
confidence: 99%
“…[24] Binding and functional parameters were calculated using Prism 5.0 software (GraphPAD, San Diego, CA, USA). IC 50 values obtained from competition curves were converted to K i values using the Cheng-Prusoff equation.…”
Section: Methodsmentioning
confidence: 99%
“…The truncated (N)-methanocarba purine analogues 99 (MRS5474) and 100 (MRS5719) showed selectivity as A 1 AR full agonist and partial agonist, respectively. 20 The 2-phenylalkynyl derivative 21 in the truncated series showed selectivity as an A 3 AR antagonist, 19,21 and the related 5′-methyluronamides 101 (MRS5697) and 102 (MRS5698) were highly selective agonists at both human and mouse A 3 ARs. 18 …”
Section: Application Of Methanocarba Templates To Ar and P2yr Ligandsmentioning
confidence: 99%
“…21 Extensive modification of this class of molecules provided various lead molecules to achieve selectivity for either the A 1 AR or the A 3 AR. 19,20 The cyclopentone derivative 22b was synthesized from D-ribose 22a in six steps (Scheme 3c), 22 a and the glycosyl sugar 22c was formed upon the stereoselective reduction of 22b by sodium borohydride in the presence of cerium(III) chloride followed by a Simmons–Smith cyclopropanation of the resulting alcohol.…”
Section: Synthetic Approaches To Methanocarba Nucleosidesmentioning
confidence: 99%